PERSEPSI PENGUNJUNG TERHADAP PENYELENGGARAAN SANUR VILLAGE FESTIVAL DI PANTAI MATAHARI TERBIT TAHUN 2022 - Fareldiego, Franky; Asmarani, I Gusti Ayu Ratih (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pariwisata Bali, 2023)
The Sanur Village Festival is an annual festival of the people of the village of Sanur Kaja organized by the Sanur Development Foundation. This study aims to determine visitor perceptions of holding the Sanur Village Festival in 2022 at Matahari Terbit Beach. This study uses a six-dimensional event method consisting of marketing materials, transportation, access and reception of guests, nuances, ambiance and decoration, food or culinary, entertainment or activities, and facilities. Data collection techniques used were interviews, documentation studies, and questionnaires with 102 respondents. The results of this study indicate that visitor perceptions of the 2022 Sanur Village Festival are good with an average score of 4.22. This is because there is a dimension that has a less good value, namely the facility dimension. Therefore, the organizers are expected to re-evaluate so that the next implementation of the Sanur Village Festival can achieve the desired goals.